Fabrication of ketoconazole nanoparticles and their activity against Malassezia furfur - PRITI PARALIKAR (Nusantara Bioscience, 2015)
Abstract. Paralikar P. 2015. Fabrication of ketoconazole nanoparticles and their activity against Malassezia furfur. Nusantara Bioscience 7: 43-47. In the present study, ketoconazole nanoparticles were synthesized from commercially available ketoconazole powder. Sonication is the physical method used to fabricate ketoconazole nanoparticles. UV-Visible spectroscopy, FTIR spectroscopy, NTA analysis, and TEM analysis reveals the formation of polydispersed ketoconazole nanoparticles with 51nm particle size. The antifungal study demonstrates that synthesized ketoconazole nanoparticles exhibit significant activity against Malassezia furfur as compared with commercially available ketoconazole powder. Further, nanogel was prepared using ketoconazole nanoparticles which showed significant antimalassezial activity. After systematic trial, the ketoconazole nanoparticles containing gel can be used as antidandruff gel.